Modulatory Actions of the Glycine Receptor β Subunit on the Positive Allosteric Modulation of Ethanol in α2 Containing Receptors - Muñoz, Braulio; Mariqueo, Trinidad; Murath, Pablo; Peters, Christian; Yevenes, Gonzalo E.; Moraga-Cid, Gustavo; Peoples, Robert W.; Aguayo, Luis G. (Frontiers in Molecular Neuroscience, 2021)
Alpha1-containing glycine receptors (GlyRs) are major mediators of synaptic inhibition in the spinal cord and brain stem. Recent studies reported the presence of α2-containing GlyRs in other brain regions, such as nucleus accumbens and cerebral cortex. GlyR activation decreases neuronal excitability associated with sensorial information, motor control, and respiratory functions; all of which are significantly altered during ethanol intoxication. We evaluated the role of β GlyR subunits and of two basic amino acid residues, K389 and R390, located in the large intracellular loop (IL) of the α2 GlyR subunit, which are important for binding and functional modulation by Gβγ, the dimer of the trimeric G protein conformation, using HEK-293 transfected cells combined with patch clamp electrophysiology. We demonstrate a new modulatory role of the β subunit on ethanol sensitivity of α2 subunits. Specifically, we found a differential allosteric modulation in homomeric α2 GlyRs compared with the α2β heteromeric conformation. Indeed, while α2 was insensitive, α2β GlyRs were substantially potentiated by ethanol, GTP-γ-S, propofol, Zn2+ and trichloroethanol. Furthermore, a Gβγ scavenger (ct-GRK2) selectively attenuated the effects of ethanol on recombinant α2β GlyRs. Mutations in an α2 GlyR co-expressed with the β subunit (α2AAβ) specifically blocked ethanol sensitivity, but not propofol potentiation. These results show a selective mechanism for low ethanol concentration effects on homomeric and heteromeric conformations of α2 GlyRs and provide a new mechanism for ethanol pharmacology, which is relevant to upper brain regions where α2 GlyRs are abundantly expressed.